Orientação semi-automática de imagens CBERS usando rodovias como controle de campo - Dal Poz, Aluir Porfírio [UNESP]; Scalco, Júlio Cesar [UNESP] (My University, 2006)
In this paper is proposed a methodology for semiautomatic CBERS image orientation using roads as ground control. It is based on an iterative strategy involving three steps. In the first step, an operator identifies on the image the ground control roads and supplies along them a few seed points, which could be sparsely and coarsely distributed. These seed points are used by the dynamic programming algorithm for extracting the ground control roads from the image. In the second step, it is established the correspondences between points describing the ground control roads and the corresponding ones extracted from the image. In the last step, the corresponding points are used to orient the CBERS image by using the DLT (Direct Linear Transformation). The two last steps are iterated until the convergence of the orientation process is verified. Experimental results showed that the proposed methodology was efficient with several test images. In all cases the orientation process converged. Moreover, the estimated orientation parameters allowed the registration of check roads with pixel accuracy or better.
Semiautomatic CBERS image orientation using roads as ground control
Keywords: CBERS image; DLT; Ground control; Image; Road extraction; algorithm; image analysis; pattern recognition; road